Effectiveness of Health Education Media on Oral Hygiene Among School-Aged Children - Ekasusanti Ekasusanti; Massatriadi Massatriadi; T Nazarullah (SEHATI: Jurnal Kesehatan, 2026)
Oral hygiene is an essential indicator of health among school-aged children and plays a significant role in preventing dental caries and other oral diseases. Inadequate toothbrushing practices, limited knowledge of oral health, and insufficient access to health education contribute to the high prevalence of dental plaque and poor oral hygiene in this population. This systematic review aimed to evaluate the effectiveness of various health education media in improving oral hygiene among school-aged children. The review was conducted in accordance with the PRISMA 2020 guidelines. A comprehensive literature search was performed in PubMed, Scopus, Web of Science, ScienceDirect, ProQuest, SpringerLink, Wiley Online Library, and Google Scholar. Articles were selected using the PICO framework, with school-aged children (6–12 years) as the population, health education media as the intervention, conventional education or no intervention as the comparator, and outcomes including oral health knowledge, toothbrushing behavior, plaque scores, oral hygiene indices, and overall oral health status. Only experimental and quasi-experimental studies published in English or Indonesian between 2016 and 2026 were included. The findings demonstrated that interactive educational media, including animated videos, educational games, smartphone-based applications, audiovisual materials, and live demonstrations, produced greater improvements in oral health knowledge, attitudes, toothbrushing skills, and reductions in plaque scores than conventional printed educational materials. Furthermore, multimodal educational approaches combined with hands-on practice achieved more sustained behavioral changes than one-way health education sessions. In conclusion, health education media are effective in improving oral hygiene among school-aged children. These findings support the integration of innovative educational media into school-based oral health promotion programs to enhance children's oral health behaviors and long-term preventive outcomes